Pelatihan pembuatan souvenir gantungan kunci berbasis daun di Desa Tahtul Yaman Kecamatan Pelayangan Kota Jambi - Revis Asra; Mahya Ihsan; Ade Adriadi; Anggit Prima Nugraha; Dawam Suprayogi (Unri Conference Series: Community Engagement, 2020)
This aims of dedication community to uplifting entrepreneurial activities in order and increas the economy of the people in Pelayangan sub-district, Jambi city. The service location is the closest location to the tourist area “Gentala Arasy” bridge which is the icon of Jambi city. Through this service, it is hoped that the community at the service location can develop this activity to increase the collection of souvenirs sold at that location. The easy process of making and the availability of abundant leaves is one of the criteria for this dedication. This activity is carried out in two stages, namely counseling and practice. The extension stage is carried out by presenting participants about the manufacturing process and the equipment used. Practical stage is working directly into a product. The result is some of key chain products that are ready to be used as souvenirs. This activity provides knowledge to the community to generate interest in entrepreneurship. All stages of the event went well and was attended by all participants. This service activity will continue to be carried out in order to improve the community's economy and to support the vision of Jambi University as a World Class & Entrepreneurship University.